2022
DOI: 10.3389/fonc.2022.971462
|View full text |Cite
|
Sign up to set email alerts
|

Matricellular protein tenascin C: Implications in glioma progression, gliomagenesis, and treatment

Abstract: Matricellular proteins are nonstructural extracellular matrix components that are expressed at low levels in normal adult tissues and are upregulated during development or under pathological conditions. Tenascin C (TNC), a matricellular protein, is a hexameric and multimodular glycoprotein with different molecular forms that is produced by alternative splicing and post-translational modifications. Malignant gliomas are the most common and aggressive primary brain cancer of the central nervous system. Despite c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 216 publications
0
5
0
Order By: Relevance
“…Post-translation modification can give rise to proteins with different functions. Notably, the small fragment obtained by proteolytic processing displays functions that can be very different from those of the full-length protein (Fu et al 2022 ). In the embryo, TNC is widely expressed in the sites of morphogenesis around motile cells, and at different degrees in connective tissues, such as bone and cartilage, and in the central nervous system.…”
Section: Ecm Molecules In Aatsmentioning
confidence: 99%
See 3 more Smart Citations
“…Post-translation modification can give rise to proteins with different functions. Notably, the small fragment obtained by proteolytic processing displays functions that can be very different from those of the full-length protein (Fu et al 2022 ). In the embryo, TNC is widely expressed in the sites of morphogenesis around motile cells, and at different degrees in connective tissues, such as bone and cartilage, and in the central nervous system.…”
Section: Ecm Molecules In Aatsmentioning
confidence: 99%
“…In the adult human organism, TNC is expressed only in connective tissues that bear tensile strength, below some epithelia and in stem cell niches, such as bone marrow, crypts of the intestine, bulge of hair follicles and bone marrow. In addition, TNC is also expressed in adult brain in both stem cells niches (astrocytes in the subventricular zone and granule cells in the hippocampus) and cerebellum (Fu et al 2022 ). TNC belongs to Tenascin family which includes Tenascin-W, Tenascin-X, and Tenascin-R.…”
Section: Ecm Molecules In Aatsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, tenascin-C is a glycoprotein that is expressed in the ECM of tissues during disease or injury, 18 and it is overexpressed in many cancer cell lines. 19 It can bind to cell surface receptors, such as toll-like receptor 4 (TLR4), which is present on stromal cells. 20 Furthermore, tenascin-C has been found in the stroma of solid tumours 21 and importantly, glioblastoma cells, such as U87-MG cells, are known to express high levels of tenascin-C. 22,23 By conjugating a peptide that can interact with tenascin-C to the surface of silver NPs, it was found that the NPs with the peptide were up taken by the U87 cells, while no uptake was observed with NPs lacking the peptide.…”
Section: Introductionmentioning
confidence: 99%